Hoxa2 Inhibits Bone Morphogenetic Protein Signaling during Osteogenic Differentiation of the Palatal Mesenchyme - Iyyanar, Paul P. R.; Nazarali, Adil J. (Frontiers in Physiology, 2017)
Cleft palate is one of the most common congenital birth defects worldwide. The homeobox (Hox) family of genes are key regulators of embryogenesis, with Hoxa2 having a direct role in secondary palate development. Hoxa2-/- mice exhibit cleft palate; however, the cellular and molecular mechanisms leading to cleft palate in Hoxa2-/- mice is largely unknown. Addressing this issue, we found that Hoxa2 regulates spatial and temporal programs of osteogenic differentiation in the developing palate by inhibiting bone morphogenetic protein (BMP) signaling dependent osteoblast markers. Expression of osteoblast markers, including Runx2, Sp7 and AlpI were increased in Hoxa2-/- palatal shelves at embryonic day (E) 13.5 and E15.5. Hoxa2-/- mouse embryonic palatal mesenchyme (MEPM) cells exhibited increased bone matrix deposition and mineralization in vitro. Moreover, loss of Hoxa2 resulted in increased osteoprogenitor cell proliferation and osteogenic commitment during early stages of palate development at E13.5. Consistent with upregulation of osteoblast markers, Hoxa2-/- palatal shelves displayed higher expression of canonical BMP signaling in vivo. Blocking BMP signaling in Hoxa2-/- primary MEPM cells using dorsomorphin restored cell proliferation and osteogenic differentiation to wild type levels. Collectively, these data demonstrate for the first time that Hoxa2 may regulate palate development by inhibiting osteogenic differentiation of palatal mesenchyme via modulating BMP signaling.